Perencanaan dan Perancangan SD Anak Emas dan MTs Generasi Emas dengan Pola Pendidikan Inklusif - Aura Titania Cintoko Gayatri; Agus Kurniawan; Made Suryanatha Prabawa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Every Indonesian citizen has the right and the obligation to get an education. However, not all students have access to receive education, one of which is students with special needs. Students with special needs need a special learning service that can suit their respective needs, so the formation of this inclusive school will provide opportunities for students with special needs to receive education together with other normal students. This inclusive education has been applied to SD Anak Emas and MTs Generasi Emas which are located in Denpasar City, but there are several problems in these two schools including; [1] several activities have not received adequate facilities to support learning activities, [2] the entrances of these two schools are located in residential areas, causing congestion, [3] the lack of green open spaces and vehicle parking spaces, [4] unorganized building zoning, [5] poor drainage/utility system that causes flooding in the school area. From the above problems, it is necessary to re-plan the latest location with the application of the concept of a fun-inclusive space to provide a pleasing design and can be used by all users of normal students and with special needs.